Indicadores de alerta temprana en Ecuador: Una metodología de cálculo - Villacís Martinez, Antonio (2000)
The purpose of this research is to build four early alert indicators, that are evaluated to determine its capacity in order to anticipate monetary crisis in Ecuador between 1993 and March 1999. The results that were found show evidence of which would be the variables that could be used as early warning indicators. The fact that the indicator M2/1MR is the most relevant in order to predict a monctary crisis, makes evident the need of a currency strongly supported by monetary reserves, and also the necessity of implementing policies that ensure the stability of this relation. Is very hard to apply this model to a dollarization scheme, because with this scheme, most of variables that helped us to determine the existence of a monetary crisis, disappear. However, the methodology and the obtained results arc usetul to analyze which where the vartables